Changes in sexuality during ulipristal acetate treatment in women with symptomatic uterine fibroids - Tuschy, Benjamin; Gabbert, Mirja; Weiß, Christel; Hornemann, Amadeus; Wuhrer, Anne; Sütterlin, Marc; Berlit, Sebastian (European journal of obstetrics & gynecology and reproductive biology, 2018)
Objective - To evaluate changes in sexuality in women treated with Ulipristal acetate (UPA) due to symptomatic uterine fibroids. - Study design - A total of 102 women with symptomatic uterine fibroids undergoing conservative therapy with UPA were enrolled in this observational study. Sexuality was evaluated before and after a three month UPA treatment using the Female Sexual Functioning Index (FSFI) as well as the Sexual Activity Questionnaire (SAQ). Before treatment was initiated, participants additionally filled in a standardised questionnaire addressing the expected changes in sexuality due to UPA. Demographic parameters, expectations concerning changes in sexuality, and FSFI- and SAQ-scores were analysed. - Results - The average age of the study collective was 42.3 years. For the majority of the included women (n=70; 71.4%) sexuality was rated as an important issue and 86 women (87.8%) did not think that UPA would have an impact on the frequency of sexual intercourse, the quality (n=91; 92.9%) or frequency of orgasms (n=87; 88.8%) neither sexual receptivity (n=88; 89.8%). Full data sets were available for 73 patients (71.6%). The FSFI showed significantly higher sub scores regarding desire (3.6±1.2 vs. 3.9±1.2; p=0.0012) and arousal (4.2±1.7 vs. 4.4±1.9; p=0.0151) as well as a higher total score (26.6±9.0 vs. 27.4±9.5; p=0.0008) after UPA treatment. Regarding the SAQ a statistically significant difference regarding the subscore “habit” was found (p<0.0001) comparing pre with post interventional scores. - Conclusion - Sexuality in general seems to be important for women with symptomatic uterine fibroids. As the treatment with UPA appears to improve sexuality, this circumstance can be mentioned in a pre-therapeutic counselling.
Gesehen am 17.06.2019